Experimental and numerical study on corona onset threshold under combined AC-DC voltages in Wire-Plane electrodes. (December 2022) - Ma, Ziyu; Xia, Junyi; He, Xuyuan; Zhou, Yunbo; He, Zichen; Li, Qi; Bian, Xingming
Highlights: The influence of conductor radius and conductor spacing on the corona onset voltage of wire-plane electrode under combined AC-DC voltages were studied. It was found that the radius affected the intercept of the corona onset voltage curve, while the conductor spacing affected the slope. The variation of corona onset voltage of the four types of corona discharge has been analyzed. It turned out that the type of corona was only related to the intercept of the corona onset curve, not the slope. The corona onset voltage of the four types corona in descending order was DC-side positive corona, DC-side negative corona, AC-side positive half-cycle corona, AC-side negative half-cycle corona. The corona model under combined AC-DC voltages has been established. The results indicated that the space charge distribution near the DC wire was even, while uneven near the AC wire. The more residual space charge was, the higher corona onset voltage would be. Abstract: With the large-scale application of hybrid HVDC/HVAC transmission technology, the phenomenon of corona discharge is also intensified. This paper attempts to provide a comprehensive understanding of the variation of corona onset voltage under combined AC-DC voltages. In this paper, an experimental platform for measuring corona onset voltage and current pulses of wire-plane electrode under combined AC-DC voltages was built. A new corona model of wire-plane electrode under combined AC-DC voltages was also established by using the fluid model and the ion flow field model. The corona onset voltages of wire-plane electrode under different ratios of AC and DC voltages, conductor radius and conductor spacing were measured. It turned out that the conductor radius affected the intercept of the corona onset curve, while the conductor spacing affected the slope. In addition, the type of corona only affected the intercept of the corona onset curve, not the slope. With the same fixed voltage of non-corona conductor, the corona onset voltage of the DC-side positive corona was the largest, followed by the DC-side negative corona, then was the AC-side positive half-cycle corona, and the smallest was the AC-side negative half-cycle corona. The interaction between AC voltage and DC voltage was approximately linear. The calculations of the model illustrated that the residual space charges had a blocking effect on corona discharge. Therefore, the more residual space charge was, the higher corona onset voltage would be.